Gait Analysis 1 Year after Primary TKA: No Difference between Gap Balancing and Measured Resection Technique - Miozzari, Hermes H.; Armand, Stéphane; Turcot, Katia; Lübbeke, Anne; Bonnefoy-Mazure, Alice (The Journal of Knee Surgery, 2019)
Mechanical alignment in total knee arthroplasty (TKA) can be achieved using dependent bone cuts. The hypothesis is that patients have a better balanced TKA, as a result. The aim of this study was to determine if this technique is superior to an independent bone cut technique in terms of gait parameters, patient-reported outcome measures (PROMs), and satisfaction assessed before surgery and at 1-year follow-up. A total of 58 patients were evaluated before and 1 year following TKA, using the Press Fit Condylar (PFC) Sigma posterior stabilizer (PS) design; 39 (70 ± 8 years; 27 women) with independent bone cuts and 19 (71 ± 7 years; 12 women) with dependent bone cuts using the Specialist TRAM. Gait was evaluated with a three-dimensional motion analysis system for spatiotemporal and kinematics parameters. Pain and functional levels were assessed using the Western Ontario and McMaster Universities arthritis index (WOMAC); general health was assessed by the short form (SF)-12. Global satisfaction, as well as patient satisfaction, related to pain and functional levels were assessed using a five-point Likert's scale. No significant difference was found between both groups in terms of age, body mass index, pain, and functional levels at baseline. At 1-year follow-up, despite an overall improvement in gait, WOMAC, SF-12 physical score and pain, none of the patients showed gait parameters comparable to a healthy control group. No surgical technique effect was observed on gait, clinical outcomes, and satisfaction level. While observing an overall improvement at 1-year follow-up, we did not find any significant difference between the two surgical techniques in terms of gait parameters, patients' outcomes, and satisfaction.
Keywords: osteoarthritis; total knee arthroplasty; knee kinematics; gait analysis; PROMs; gap balancing; resection technique